Unsurpassed Heterosexism Within E. Lévinas’ Work - Idareta Goldaracena, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
As a likely result of the turn towards rational ethics experienced during the last few decades,the thought of Jewish philosopher Emmanuel Lévinas is currently growing in popularity. After a critical lecture of his work closely following feminist hermeneutics, we will focus our attention upon the evolution of Lévinas’ treatment of women and the feminine in order to demonstrate that the inherent sexism of his ethical proposal commonly found in his earlier work, is not surpassed by the heterosexist binomial «the saying and the said» which articulates his definite ethical proposal concerning sensibility and vigilance.